2009
DOI: 10.1158/1055-9965.epi-08-0705
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Cytokines and Lung Cancer Survival in African Americans and Caucasians

Abstract: Accumulating evidence suggests a role for inflammation in the development and progression of cancer. Our group recently identified a cytokine gene signature in lung tissue associated with lung cancer prognosis. Therefore, we hypothesized that concentrations of circulating cytokines in serum may be associated with lung cancer survival. Ten serum cytokines, namely, interleukin (IL)-1B, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12, granulocyte macrophage colony-stimulating factor, interferon (IFN)-;, and tumor necrosis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
72
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 46 publications
11
72
1
2
Order By: Relevance
“…An important contributing factor to this may have been the relatively low dose used here in contrast to other studies. 10,24 In line with earlier studies showing increased circulating IL-6, IL-8, and/or IL-10 levels in advanced cancer patients, 25,26 pretreatment values of these cytokines were Oncolytic Ad5/3-Cox2L-D24 in cancer patients S Pesonen et al somewhat elevated in the majority of patients. Rapid elevation in IL-6 or TNF-a indicates an acute inflammatory response and these cytokines may be sensitive markers of clinical or subclinical adenovirus toxicity.…”
Section: Discussionsupporting
confidence: 59%
“…An important contributing factor to this may have been the relatively low dose used here in contrast to other studies. 10,24 In line with earlier studies showing increased circulating IL-6, IL-8, and/or IL-10 levels in advanced cancer patients, 25,26 pretreatment values of these cytokines were Oncolytic Ad5/3-Cox2L-D24 in cancer patients S Pesonen et al somewhat elevated in the majority of patients. Rapid elevation in IL-6 or TNF-a indicates an acute inflammatory response and these cytokines may be sensitive markers of clinical or subclinical adenovirus toxicity.…”
Section: Discussionsupporting
confidence: 59%
“…Crohns et al (2010) showed that levels of IL-6 and other cytokines may be involved in prognosis in lung cancer patients. Enewold et al (2009) hypothesized that high serum levels of IL-6, IL-10, IL-12, and TNF-a are correlated with poor prognosis of lung cancer in African Americans and Caucasians. Thus, it can be deduced that high IL-6 levels in the peripheral circulation is related to a worse response to chemotherapy and poor clinical prognosis in NSCLC patients (Liu et al, 2012;Zarogoulidis et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Levels of IL-6 are likely to be influenced by several behavioral and genetic factors. [1][2][3][4][5][6][7][8][9][10][11] Associations between common gene variations in IL-6 and race/ethnicity have been examined in several studies but with inconsistent findings, and these studies did not focus on people living with HIV (PLWH). [4][5][6] Saijo et al 7 studied 347 Japanese individuals; Friedlander et al 8 studied 475 Israeli families; and the AIRGENE study targeted Europeans with myocardial infarct.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Associations between common gene variations in IL-6 and race/ethnicity have been examined in several studies but with inconsistent findings, and these studies did not focus on people living with HIV (PLWH). [4][5][6] Saijo et al 7 studied 347 Japanese individuals; Friedlander et al 8 studied 475 Israeli families; and the AIRGENE study targeted Europeans with myocardial infarct. [7][8][9][10] Also, potential factors associated with IL-6 elevations have been analyzed by Neuhaus et al 11 using three large US cohorts of people with and without HIV.…”
Section: Introductionmentioning
confidence: 99%